Perancangan dan Implementasi Sistem Informasi Persediaan Barang UMKM Rajut Berbasis Visual Foxpro - Agnemas Yusoep Islami; Sri Anawati; Noviyanti Noviyanti; Artika Sari Devy; Apriliana Apriliana; Intan Pandini; Lestiara Kamilah Syari; Rana Auliana Sari; Silvy Aprilianti (CV. ITTC INDONESIA, 2026)
Inventory management is an essential aspect of supporting MSME operations. Little Grande Craft Shop, an MSME selling knitting supplies, still manages stock records and monitoring manually, which may cause recording errors, delayed updates, and less effective inventory control. An inventory information system using Microsoft Visual FoxPro 9.0 was developed to support more effective and integrated management. The method included observation, interviews, system analysis, database and interface design using ERD and HIPO, and system implementation. The system provides login, product management, incoming and outgoing goods recording, sales transactions, automatic stock calculation, and inventory and sales reports. Implementation made inventory management more structured, improved stock information accuracy, and supported more efficient reporting.